Vehicle Computing: Vision and challenges - Sidi Lu; Weisong Shi (Journal of Information and Intelligence, 2023)
Vehicles have been majorly used for transportation in the last century. With the proliferation of onboard computing and communication capabilities, we envision that future connected vehicles (CVs) will be serving as a mobile computing platform in addition to their conventional transportation role for the next century. In this article, we present the vision of Vehicle Computing, i.e., CVs are the perfect computation platforms, and connected devices/things with limited computation capacities can rely on surrounding CVs to perform complex computational tasks. We also discuss Vehicle Computing from several aspects, including several case studies, key enabling technologies, a potential business model, a general computing framework, and open challenges.